Influences of suction pipe structures on hydraulic performance and internal flow of electric coolant pumps - Yang, Anlong; Gu, Yandong; Cheng, Li; Zhao, Wenpeng (Frontiers in Energy Research, 2024)
An electric coolant pump (ECP) serves as a critical component in the thermal management of electric vehicles. To fulfill the requirements of pressurizing and circulating coolant for various components, a complex structure with multiple pipes is integrated into the pump inlet. This study focuses on the design and analysis of three suction pipe structures: a straight pipe (Case A), a bend (Case B), and a combination of a bend with manifolds (Case C). The objective of this study is to explore the impacts of suction pipe structures on the hydraulic performance, flow pattern, temperature distribution, and vorticity of ECP. Taking into account the variability of coolant physical parameters with temperature, ECP is numerically simulated using the unsteady Reynolds-averaged Navier–Stokes (RANS) equation and the shear stress transport k–ω turbulence model. The experimental and numerical results exhibit good agreement. Case A demonstrates the highest efficiency, Case B follows as the second most efficient, and Case C displays the lowest efficiency. However, the pressure rise remains essentially consistent in all cases. The average efficiencies of Cases B and C are 1.18% and 2.13% lower than that of Case A. The temperature of ECP increases with an increase in the coolant temperature. The temperature of the printed circuit board (PCB) surpasses that of the motor. Case A exhibits the most favorable flow pattern, while Case C demonstrates the least favorable. The bend introduces secondary flow, further intensified by the manifold, leading to an increase in vorticity. The high-vorticity zones expand as the flow rate increases. This study offers valuable insights into the optimization of the ECP suction pipe structure.